Зубы на языке. Семантика острого в традиционном жилище цаатанов Монголии : TEETH ON TONGUE. THE SEMANTICS OF ACUTE IN TRADITIONAL HOUSE TSAATANS OF MONGOLIA - Дмитрий Викторович Канунников (Современные этнические процессы на территории центральной Азии: проблемы и перспективы, 2019)
Предмет статьи — апотропейная практика цаатанов, тувинцев-оленеводов Монголии, применяемая ими для магической защиты входа в жилище. В статье проводится сравнение с аналогичными практиками иных этнических групп, а также исследуется место этой практики в картине мира цаатанов, ее положение в традиционном мифоритуальном комплексе, связанном с бытом и хозяйством саянских оленеводов. : The object of the article is the apotropy practice which is used by Tsaatans, the people of Mongolian reindeer herders, for establishing of the magical defense on the entrance of theirs traditional nomadic tent. The practice includes placing of the head of large salmon (taymen) over the entrance as the apotropy. The custom is compared in the article with similar practices in different etnic groups and is considered as a part of the Tsaatans cosmology, of the traditional complex of mythological ideas and rites, which are tied together with life and household of the reindeer herders of the Sayan mountains of Mongolia and Tuwa.